MODERN APPROACHES TO CORRECTING HYPERANDROGENISM IN WOMEN - Boboqulova, S.B. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Objective of the study: To evaluate the efficacy of treatment using combined oral contraceptives containing drospirenone in anti-androgen therapy. Materials and methods. Anamnestic-clinical and laboratory research methods were conducted on 126 women of reproductive age with signs of hyperandrogenism who sought treatment at the reproductive department of the Bukhara Territorial Branch of the Republican Specialized Scientific and Practical Center for Maternal and Child Health Protection, as well as on 32 healthy women of the same age without reproductive disorders as a control group. Conclusion. The results of our study also confirmed that carefully selected combined oral contraceptives containing drospirenone are effective as anti-androgenic therapy for treating dermatopathies and menstrual cycle disorders observed in hyperandrogenism syndrome. Notably, the incorporation of lifestyle modifications and vitamin D supplementation into the treatment regimen enhanced the overall effectiveness of the therapy.